Three polymethoxyflavones from the peel of Citrus reticulata “Chachi” inhibits oxidized low-density lipoprotein-induced macrophage-derived foam cell formation - Liang, Pu-Lin; Liang, Qian-Wen; He, Pei-Wen; Chen, Xue-Lian; Xu, Ya; Tu, Hai-Sheng; Zhang, Liang; Qiu, Xiao-Hui; Zhang, Jing; Huang, Zhi-Hai; Xu, Wen (Frontiers in Cardiovascular Medicine, 2022)
Foam cell formation is the hallmark of the development and progression of atherosclerosis. The aim of the present study was to investigate the regulatory effects of three polymethoxyflavones (PMFs), namely tangeretin (TAN), 5,6,7,3',4',5'-hexamethoxyflavone (HxMF) and 3,5,6,7,8,3',4'-heptamethoxyflavone (HpMF) on macrophage-derived foam cell formation and to further explore the molecular mechanisms. The RAW264.7 macrophage-derived foam cell model was successfully induced by ox-LDL (80 μg/mL). It showed that TAN, HxMF and HpMF alleviated ox-LDL-induced NO release while also inhibiting the expression of IL-1β, IL-6 and TNF-α in RAW264.7 cells. Uptake of excess ox-LDL was inhibited by TAN, HxMF and HpMF, resulting in the reduction of its foam cell formation. Also, TAN, HxMF and HpMF promoted HDL-mediated cholesterol efflux. Western blot experiment showed that TAN, HxMF and HpMF inhibited the expression of SRA1 and CD36, while upregulating PPARγ, LXRα, ABCG1 and SRB1 expression. Together, our findings suggested that PMFs inhibited foam cell formation might inhibit lipid uptake via down-regulating SRA1/CD36 expression and promote cholesterol efflux from foam cells via up-regulating PPARγ/LXRα/ABCG1/SRB1 expression. This anti-atherosclerotic activity is expected to provide new insights into the development of healthcare uses for PMFs.